Power Generation from Solid Fuels - Spliethoff, Hartmut; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Power Generation from Solid Fuels introduces the different technologies to produce heat and power from solid fossil (hard coal, brown coal) and renewable (biomass, waste) fuels, such as combustion and gasification, steam power plants and combined cycles etc. The book discusses technologies with regard to their efficiency, emissions, operational behavior, residues and costs. Besides proven state of the art processes, the focus is on the potential of new technologies currently under development or demonstration. The main motivation of the book is to explain the technical possibilities for reducing CO2 emissions from solid fuels. The strategies which are treated are: more efficient power and heat generation technologies, processes for the utilisation of renewable solid fuels, such as biomass and waste, and technologies for carbon capture and storage. Power Generation from Solid Fuels provides, both to academia and industry, a concise treatment of industrial combustion of all types of solid, hopefully inspiring the next generation of engineers and scientists.
Motivation -- Solid Fuels -- Thermodynamics Fundamentals -- Steam Power Stations for Electricity and Heat Generation -- Combustion Systems for Solid Fossil Fuels -- Power Generation from Biomass and Waste -- Coal-Fuelled Combined Cycle Power Plants -- Carbon Capture and Storage (CCS).
Keywords: Energy systems; Power electronics; Renewable energy resources; Energy policy; Energy and state; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Energy Systems; Power Electronics, Electrical Machines and Networks; Renewable and Green Energy; Energy Policy, Economics and Management; Engineering Thermodynamics, Heat and Mass Transfer; Renewable and Green Energy